Strontium Ion-Selective Electrode Based on 18-Crown-6 in PVC Matrix - Hossein Arbab-Zavar, Mohammad; Hossein Rounaghi, Gholam; Fahmideh-Rad, Elham (Asian Journal of Chemistry, 2010)
A potentiometric strontium-selective electrode based on 18-crown-6 in PVC matrix for measurement of strontium ion is reported. The electrode was prepared by coating the surface of a graphite by a membrane containing dioctylphthalate (DOP), 18-crown-6 and carbon powder in poly(vinyl chloride) (PVC) in tetrahydrofuran (THF). The membrane composition consisting of 18-crown-6, PVC, DOP, carbon, the thickness of coated membrane, effect of pH and possible interfering cations and anions were investigated and optimized electrode were evaluated. The electrode exhibits significantly enhanced response toward strontium ions over the concentration range 1 × 10-7 to 1 × 10-2 M with slope of 27.35 mV per decade change. Fast and stable response, good reproducibility, long-term stability is demonstrated. The electrode has a response time of 20-25 s and can be used for at least 6 weeks without any considerable divergence in their potential response. The proposed electrode shows fairly good discrimination of strontium from several cations. The electrode was used for direct potentiometric measurements of strontium ions over the concentration range 1 × 10-7–1 × 10-2 M. The practical utility of the electrode has been demonstrated by using it successfully as an indicator electrode in the potentiometric titration of Sr2+ with EDTA.